The assortment policy formation as an element of the enterprise competition strategy - Ribachuk-Yarova, Tatiana; Polinchyk-Yarova, Tatiana (My University, 2019)
У статті розглянуто основні підходи до понятійного апарату "асортиментна політика". Ефективне та стабільне функціонування буле досягнуто завдяки продажу товарного асортименту на основі поєднання потреб споживачів та підприємницьких можливостей суб'єктів господарювання. Система управління асортиментною політикою передбачає розробку стратегії для кожної товарної групи. Його реалізація передбачає управління асортиментом продукції за стадіями її життєвого циклу з використанням відповідних методів її розробки. Визначено ряд факторів, що впливають на його формування. Розглянуто шляхи її реалізації, запропоновано інтегровану модель оцінки управління. The article deals with the basic approaches to the conceptual apparatus "assortment policy". The term conclusions clarification has been made. It has been estimated that the assortment policy has been aimed at the number of enterprise goals solving in order to realize the main purpose of its activity. The effective and stable functioning has been achieved through the sale of the products range based on a combination of consumer needs and of business entities entrepreneurial capabilities. The assortment policy management system provides for the development of a strategy for each product group. Its implementation involves the range products managing by its life cycle stages using appropriate methods of its development. The number of factors that influence its formation have been identified. The ways of its realization have been considered. The integrated management evaluation model has been proposed.
Keywords: кафедра економіки праці та менеджменту; assortment policy; commodity portfolio management; model; strategy; асортиментна політика; управління товарним портфелем; модель; стратегія